[tex]a).(2 \sqrt{3} +x)^2=(2 \sqrt{3} )^2+2*2 \sqrt{3} *x+x^2=12+4x \sqrt{3} +x^2 \\ \\ b).(3 \sqrt{3} x+2 \sqrt{5} )^2=(3 \sqrt{3} x)^2+2*3 \sqrt{3} x*2 \sqrt{5} +(2 \sqrt{5} )^2= \\ \\ =27x^2+12x \sqrt{15} +20 \\ \\ c).( \frac{1}{2} x+3)^2=( \frac{1}{2} x)^2+2* \frac{1}{2} x*3+3^2= \frac{1}{4} x^2+3x+9 \\ \\ d)(3-2 \sqrt{3} )=3^2-2*3*2 \sqrt{3} +(2 \sqrt{3} )^2=9-12 \sqrt{3} +12=21-12 \sqrt{3} [/tex]
[tex]e).(2 \sqrt{5} -3 \sqrt{2} x)^2=(2 \sqrt{5} )^2-2*2 \sqrt{5} *3 \sqrt{2} x+(3 \sqrt{2} x)^2= \\ \\ =20-12x \sqrt{10} +18x^2 \\ \\ f).(5 \sqrt{2} x-4 \sqrt{3} y)^2=(5 \sqrt{2} x)^2-2*5 \sqrt{2} x*4 \sqrt{3} y+(4 \sqrt{3} y)^2= \\ \\ =50x^2-40xy+48y^2[/tex]